Examining the Influence of the Marketing Mix (4PS) on Manufacturers' Purchase Decisions of Imported Tobacco: A Case Study of PT Harum Tembakau Indonesia - Jeri Cahyadi Saputra; Dudi Amarullah; Nikita Astria (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The tobacco industry is a strategic sector in Indonesia, contributing significantly to state revenue and employment absorption. Although Indonesia is known as a major tobacco producer, the demand from cigarette manufacturers for specific types of tobacco has driven imports from countries such Tiongkok, Brasil, India, Zimbabwe and Turki. PT Harum Tembakau Indonesia, a newly established company in 2024, was founded to meet this demand by supplying imported tobacco to manufacturers. In facing competition with more established firms, an effective marketing strategy becomes critically important. This study aims to analyze the influence of the marketing mix (product, price, place/distribution, and promotion) on manufacturers' purchase decisions regarding imported tobacco, with a case study on PT Harum Tembakau Indonesia. This research adopts a quantitative method using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The findings indicate that the variable place (distribution) has a positive and significant effect on purchase decision (β = 0.296; p = 0.006), while price does not show a significant influence (β = 0.120; p = 0.391). Interestingly, product (β = -0.386; p = 0.019) and promotion (β = -0.310; p = 0.001) exhibit negative and significant effects on purchase decision. The R² value of 0.225 suggests that the marketing mix model explains 22.5% of the variance in purchase decisions. These results have strategic implications, highlighting the need for the company to emphasize distribution reliability and to re-evaluate its product and promotion strategies to better align with the needs and expectations of manufacturers. This study is expected to serve as a reference for formulating more effective marketing strategies in the future.